WEB-BASED JOURNALS IN THE CLASSROOM: MOTIVATION AND AUTONOMOUS LEARNING - Pollard, Andrew (Universitas Pendidikan Indonesia, 2015)
Abstract: The use of Web 2.0 in the language classroom is an area of exploration and interest to many. In recent years, much research has looked at the use of blogs in the assistance of language development, and this paper continues in a similar fashion. One key area where this paper adds to the field however, is that it looks at a Web 2.0 portal specifically aimed at language learners; the portal in question is Lang-8, which in conjunction with being similar to a blogging platform, also provides similar functions to a social networking service. This research exposed 12 Korean participants to Lang-8 as part of a credit-bearing university writing course. The participants made weekly journal entries on Lang-8, and upon completion of the course, were given an anonymous online survey to complete. The survey addressed areas relating to online language journals, corrective feedback, motivation, and learner autonomy. Overall, the participants reported that the use of Lang-8 positively affected their motivation levels, had positive experiences through received varied corrective feedback, and were exposed to a portal that allowed for more autonomous learning.Â